Using The “Smart Robot “Method in Teaching Programming Languages - Kamalova Nilufar Ilkhomovna (Zien Journals, 2021)
The advantages of using interactive methods in programming teaching and the procedure for interactive using the “smart robot “method is given in the article.
Keywords: Innovative educational technologies; interactive methods; python; smart robot